Comparison of Matching Layers for Extended Hemispherical Lenses in Beam Scanning Applications - Kar, S.; Sonmez, N. T.; Mambet, S.; Tokan, N. T. (IEEE, 2016)
This paper examines the beam scanning performance of the matching layers designed on millimeter wave integrated lens antennas with dense material. Millimeter wave extended hemispherical lens antenna made of alumina is coated with different types of solutions for antireflection layers. The lens is illuminated by an aperture coupled lens antenna designed to radiate into alumina at 77GHz. The role of matching layers is demonstrated. A frequency-dependence characterization of the beam pattern clearly showed the existence and impact of internal reflections on beam scanning performance.
Keywords: matching layer; millimeter wave; lens; corrugations; stereolithography; extended hemispherical lens; beam scanning; ANTENNAS; Computer Science; Engineering; Telecommunications